Plyometrics - Chu, Donald A. (Donald Allen) 1940-; Myer, Gregory D. (Human Kinetics, 2013)
Presents science-based and tested exercises and programmes to ensure optimal power with minimal risk of injury. This guide for designing plyometric programmes also includes sport-specific power training regimes for basketball, soccer, football, rugby and volleyball, and shows how to integrate those plans into a total athlete development programme